Social Security Measures for Workers of Unorganised Sector in Kerala - Diti Goswami
Kerala has a commendable history in its approach to reaching out to the vulnerable sections using a number of innovative social security measures. One of these is the Welfare Funds Model for informal sector workers. This paper evaluates the present scenario of this Welfare Fund Model in Kerala and its various implications. It also highlights the fact that even though this approach is palpable and can be visualised as an institutional innovation, it has many limitations which need to be solved.